A Vintage Model of the Demand for Energy and Employment in Australian Manufacturing Industry - Hawkins, R. G. (Review of Economic Studies, 1978)
Journal Article A Vintage Model of the Demand for Energy and Employment in Australian Manufacturing Industry Get access R. G. Hawkins R. G. Hawkins Australian National University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 3, October 1978, Pages 479–494, https://doi.org/10.2307/2297250 Published: 01 October 1978 Article history Received: 01 July 1976 Accepted: 01 November 1977 Published: 01 October 1978